2022
DOI: 10.2147/ndt.s347356
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Depression in the Elderly: Practical Guidance and Challenges for Clinical Management

Abstract: Depression is one of the most common mood disorders in the late-life population and is associated with poor quality of life and increased morbidity, disability and mortality. Nevertheless, in older adults, it often remains undetected and untreated. This narrative review aims at giving an overview on the main definitions, clinical manifestations, risk and protective factors for depression in the elderly, and at discussing the main reasons for its under/misdiagnosis, such as cognitive decline and their overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 80 publications
(135 reference statements)
0
4
0
7
Order By: Relevance
“…However, this rate escalates with advancing age, reaching its peak at 27% among individuals over 85 years of age. [36] In a study conducted with 271 patients, it was found that participants aged over 80 were at a higher risk of depression compared to those under 80. [37] The prevalence of depression and anxiety among cancer patients is statistically significant higher compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this rate escalates with advancing age, reaching its peak at 27% among individuals over 85 years of age. [36] In a study conducted with 271 patients, it was found that participants aged over 80 were at a higher risk of depression compared to those under 80. [37] The prevalence of depression and anxiety among cancer patients is statistically significant higher compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, this rate escalates with advancing age, reaching its peak at 27% among individuals over 85 years of age. [36] In a study conducted with 271 patients, it was found that participants aged over 80 were at a higher risk of depression compared to those under 80. [37]…”
Section: Discussionmentioning
confidence: 99%
“…However, switches in diet, as well as advancing age, cause changes in the number of individual genera. For example, an increase in the abundance of the bile-tolerant species from the Bacteroidetes phylum belonging to such genera as Bacteroides and Alistipes , and Bilophila from the Proteobacteria , and a decrease in Firmicutes are associated with protein- and fat-enriched diet [ 62 ]. In turn, the gut microbiota of the elderly is characterized by a decreased Bacteroides to Firmicutes ratio, and most of all, reduced Bifidobacterium abundance, amylolytic activity, and SCFA production as well as an increase in the abundance of Gram-negative rods from Enterobacteriaceae .…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…In dementia, symptoms tend to have a slower onset, while depression symptoms typically manifest more rapidly [34]. Another important clue is that patients with depression often complain more about cognitive impairments, whereas individuals with dementia frequently deny any memory complaints and state that they sought medical attention because of their family's concerns [35]. In this case, the patient's family could not provide precise information about the onset of the patient's symptoms, but the patient did not have significant complaints, and it was their family who brought them to the hospital.…”
Section: Appraisalmentioning
confidence: 99%